Integration of Problem-Based Learning and Simulation Software - An Application of MIKE WEST® in Wastewater Engineering Education - Mo, Jinyuan (My University, 2024)
Wastewater treatment is a complex field that requires a deep understanding of both biological processes and practical applications. This thesis investigates the role of Problem-Based Learning (PBL) and wastewater simulation software in enhancing wastewater engineering education. The focus is on teaching nitrogen removal processes through traditional biological treatment methods, specifically the activated sludge process. By integrating the wastewater simulation software, students can simulate real-world wastewater treatment scenarios, enabling them to better understand the interactions between operational parameters, microbial activity, and treatment outcomes. A mixed-method approach was used to evaluate the effectiveness of this teaching method, combining student feedback from questionnaires with performance assessments during practical sessions. The results indicate a significant correlation between skills development and overall course satisfaction, highlighting the positive impact of simulation software such as MIKE WEST on students’ ability to apply theoretical knowledge to practical challenges. However, lower scores in engagement and participation may be attributed to practical constraints faced during the session, including time limitations, no prior experience with the software, and students' different study paces, which may have limited the depth of exploration. The thesis concludes that wastewater simulation software is a valuable tool for wastewater engineering education, particularly in fostering practical skills in students’ future careers and reinforcing their theoretical knowledge. Nonetheless, improvements in teaching strategies, particularly in adapting different study paces, are recommended to further optimize learning outcomes. This study provides insights into the integration of simulation software in engineering education and its potential to bridge the gap between theoretical understanding and practical application